THE TESTING OF ENTREPRENEURSHIP AS THE ATTEMPT TO REMODEL THE FACTOR OF PRODUCTION IN THE RICE FARMING - Darmadji, Darmadji; Suwarta, Suwarta (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2018)
The objective of this study was to test whether entrepreneurship can be included as a new production factor in farming business management. This study was intended to make improvement of classic economic factors of production. To achieve the purpose, the research was conducted on the rice farming at Pakis and Karangploso districts of Malang Regency, East Java. Methods analysis used were Structural Equation Modeling (SEM) with PLS smart program. Primary data was collected from the farmers by interviews based on a list of prepared questions. The analysis result showed that entrepreneurship had direct effect to increase on the performance of paddy farming. This result makes more reinforced to incorporate entrepreneurship as new factor of production in farm management. The classic theory of factor of production was important to be updated because there are many empirical facts that conceptually had influence to the farming production. One of empirical facts was internal potential that owned by every farmer which is called as entrepreneurship spirit.